The Renewing of Usul al-Fiqh: Challenges, Limitations and Future Directions - Bakar, Alyasa Abu; Sahman, S (Indonesian Journal of Islamic Economic Law, 2024)
This research aims to explore and analyse the renewing of the usul fiqh method in Indonesia, which expands the sources of law and aligns the methods of interpretation of Islamic law. The research method used is a qualitative ap-proach involving data collection techniques through literature studies and analy-sis of classical and contemporary texts. The data analysis included descriptive and critical analyses of the legal sources of the Qur'an, Hadith and the practices of companions and istinbath methods. The findings of this research are that the classical usul fiqh method requires revision, especially in terms of the criteria for determining legal verses and the much-debated concept of nasikh-mansukh, so that the application of maqashid sharia and Hadith matan criticism is essential to ensure the relevance and validity of Islamic law in the contemporary context. In addition, this research highlights the dilemmas of legal istinbath authority, in-cluding the challenges of implementing just and humane laws in a country with a diverse Muslim population. The contribution of this research is the recommenda-tion of an integrative and holistic approach to the renewal of usul fiqh through the selective acceptance of new methods of thinking, such as hermeneutics and statistics, as a basis for formulating legal facts so that the validity of Islamic law and its application not only remain rooted in originality but also relevant to con-temporary life.